Survival gain with re-Op/RT for recurred high-grade gliomas depends upon risk groups. Issue 2 (August 2018) - Chun, Seok-Joo; Park, Sung-Hye; Park, Chul-Kee; Kim, Jin Wook; Kim, Tae Min; Choi, Seung Hong; Lee, Soon-Tae; Kim, Il Han
Abstract: Introduction: A majority of high-grade gliomas relapse despite combined surgery, radiotherapy and chemotherapy. There is no consensus on standard treatment for recurrent high-grade gliomas, or defined efficacy of adjuvant re-RT after re-Op. This retrospective study evaluated the benefit and safety of re-RT after re-Op (re-Op/RT). Materials and methods: A total of 84 patients with recurrent high-grade gliomas who underwent reoperation from 2009 to 2015 were analyzed. All patients received neurosurgical intervention and adjuvant radiotherapy previously before recurrence. At recurrence and after reoperation, treatment options were discussed in multidisciplinary clinic or brain tumor joint conference. For re-RT, cumulative EQD2 (equivalent dose in 2 Gy fractions at α / β  = 2) was below 106.9 Gy. Result: Median progression free survival (PFS) was 6.5 months; 3.5 months with re-Op, 9.0 months with re-Op/RT ( p  = 0.025). Age <50, time interval to recur ≥12 months, WHO pathologic grade III, methylated MGMT promotor, and re-RT were factors enhancing PFS in the multivariate analysis. Median overall survival (OS) was 18.3 months: 12.7 months with re-Op, and 28.1 months with re-Op/RT ( p  = 0.066). Three risk factors (age >50, WHO grade IV, and unmethylated promoter of MGMT) were significantly associated with poor OS in multivariate analysis. Benefit of re-RT in both OS and PFS was established in patients carrying 2 or more risk factors. During re-RT, 4 patients (8%) had grade 2 or higher toxicity, and 3 patients (6%) did not complete re-RT. No radionecrosis was observed. Conclusion: Re-RT after re-Op was tolerable with a cumulative median EQD2 of 99.3 Gy and resulted in clear benefit in PFS and marginal gain in OS. Survival gain with re-Op/RT was more prominent in patients with two or more risk factors (age ≥50, WHO pathologic grade IV, unmethylated MGMT promoter), and needs to be validated.